Struktur Retorika Karangan Narasi Mahasiswa Pendidikan Guru Sekolah Dasar STKIP PGRI Lubuklinggau - Murti, Sri (Institut Agama Islam Negeri (iAIN) Curup, 2018)
The research aims was to describe the structure of a Narrative Essay rhetoric Describing Student primary school teacher education STKIP PGRI Lubuklinggau, using qualitative research methods. As for the steps in analyzing the following: a). data analysis will be started from an analysis of the